Does well-child care education improve consultations and medication management for childhood fever and common infections? A systematic review. - Peetoom, K; Smits, J; Ploum, L; Verbakel, J; Dinant, G; Cals, J (BMJ Publishing Group, 2017)
Background Fever is common in preschool children and is often caused by benign self-limiting infections. Parents’ lack of knowledge and fever phobia leads to high healthcare consumption. Objective To systematically review the effect of providing educational interventions about childhood fever and common infections in well-child clinics (WCCs), prior to illness episodes, on parental practices: healthcare-seeking behaviour (frequency of physician consultations, appropriateness of consultations) and medication management. Design Medline, Embase, CINAHL, PsycINFO, Cochrane Library, Web of Science were searched. We included randomised controlled trials evaluating interventions in WCC settings focusing on educating parents prior to new illness episodes to improve parental practices during episodes of childhood fever and common infections. Data were extracted on study design, sample characteristics, type of intervention, outcome measures and results. Results Eight studies were eligible for data extraction. Educating parents, in WCCs, prior to new episodes of childhood fever and common infections reduces daytime physician consultations of parents, home visits and telephone consultations, and enhances medication management. However, single and multicomponent interventions vary in effectiveness in reducing the frequency of daytime physician consultations and differ in their potential to reduce the number of home visits and general practitioner out-of-hours contacts. Only multicomponent interventions achieved a reduction in telephone consultations and improved medication management. Conclusions Educating parents in WCCs prior to episodes of childhood fever and common infections showed potential to improve parental practices in terms of healthcare-seeking behaviour and medication management.